Typology of Grave Forms in Peneleh European Cemetery Area Case Study: Peneleh European Cemetery Area Surabaya - Yayan Indrayana; RA Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
Peneleh European Cemetery in Surabaya is the oldest European cemetery whose existence is very important for the historical narrative of Surabaya City. With an area of almost 4.5 hectares, this cemetery has a large number of tombs, with very diverse shapes. From the diversity of the shape of the gravestone and the shape of the tomb when viewed visually has many similarities and differences, but there has never been a record that mentions the exact number of typological forms of the tomb, so a study is needed that can classify various kinds of typological forms of the tomb. The classification of this tomb shape needs to be done immediately considering the condition of the tombs in the Peneleh European Cemetery is increasingly threatened by its physical form. In classifying or researching the typology of Peneleh Tombs, data collection can be done by several methods, especially the direct observation method to each tomb and then measuring, recording and describing its shape. Another thing that needs to be done to determine the typology of these tombs considering that many are no longer intact is the search for old data, both in the form of records, maps and also photos that can be used for comparison or comparison with current conditions. Recording based on interviews, especially with residents in the Peneleh area, is also an important thing to do considering that in memory they have an idea of how the shape and condition of the tombs 10-20 years ago. Related to the Typology of Tombs, when associated with the development plan of Peneleh European Tombs into one of the Historic tourist destinations in Surabaya City, the determination of Typology is very important because it can be a guide or source of data that can be used for the preference of the management in this case the Surabaya City government when going through the process of revitalization and repair of Tombs. In addition, research on the typology of this tomb will be the basis for the development of thematic tourism in the Peneleh Cemetery area.